Comparative Study of the Impact of Economic, Social and Physical Dimensions of Border Markets on the Quality of Life of Border Residents - Mousavi Parsaie, Seyed Mohammad; Pallás, Edit Ilona; Molnár, Csilla (Acta Carolus Robertus, 2025)
Border markets at border points near authorized customs can provide a space for citizens on both sides of the border to conduct transactions while adhering to regulations. The effects of such border markets can affect the quality of life of border residents. This article aims to conduct a comparative examination of the economic, social and physical dimensions of border markets and their impact on the quality of life of border residents. The predominant research approach in terms of method is descriptive-analytical. Indicators and items have been determined based on the research questions and objectives in economic, social and physical dimensions, totaling sixteen indicators are determined for assessment and investigation. The SPSS software was utilized for data analysis and the statistical population consists of household heads working in the markets of Golestan province, Iran, 5621 individuals, with a sample size of 384 determined using Cochran's formula. The research results indicate that the performance of border markets in Golestan province has not uniformly influenced the examined indicators. Enter Regression results in ranking the impact of Golestan province's border market suggest that the economic variable explains the highest impact at 47%, followed by the social variable at 35%, and the physical variable at 21%. Golestan province's border markets have successfully influenced the improvement of the quality of life, as the calculated significance level is less than 0.05. This research can serve as a reliable criterion for regional planners, especially in border areas. To this end, recommendations are also provided.
Keywords: sustainable development; empowerment; job creation; quality of infrastructure and housing